Indução da lactação em vacas: perfil endócrino e de marcadores inflamatórios - Pestano, Henrique Schneider (2017)
The first attempts of artificial induction of lactation (AIL) in cows have been performed in the decades of 40 and 60, and sought to mimic the endocrine profile of the final period of gestation, enabling the lactation in the absence of a pregnancy. The technique has numerous advantages, such as being more financially feasible than the purchase of heifers, avoids culling of high genetic merit cows, extends the productive life of cows and allows females to get pregnant after the protocol. Even with so many advantages, the induction protocols had little evolution, being the technique sub utilized. Some limitations of the technique include injuries and fractures of some animals submitted to protocols, nonresponsiveness of some animals, milk production 20 to 30% lower than a natural lactation, intense animal handling and hormonal applications that result in long period of estrus. Based on the above mentioned, the objective of this study was to determine the endocrine profile and alterations in stress and inflammation markers caused by AIL technique. Furthermore, it was investigated an alternative to replace the application of injectable progesterone. In a first study, five cows were subjected to a conventional protocol for induction of lactation (IND) and six served as control (CON), receiving only one intravaginal device (DIV) containing 1g of progesterone (P4). Blood samples were collected and thermograms were recorded from the sites of hormones application and from the left hind hoof of each animal over 14 days. The females subjected to the protocol showed mammary gland development and estrus manifestation for approximately 12 days starting on day 9. It was found that there was no statistical difference in relation to cortisol, cholesterol, albumin, serum protein, and paraoxonase between the cows IND and CON (P>0.05). Regarding the endocrine profile, the cows IND presented lower levels of estradiol in D0 (51.9±16 pg/ml) in relation to days 2, 4, 8 and 12 (above 2000pg/ml; P<0.05). The levels of progesterone in cows IND at D4 (9.4±1,6ng/ml) were significantly higher than those observed in the same moment in CON cows (4.2±0,3ng/ml; P<0.05). Based on the observed progesterone endocrine profile in experiment 1, in a second experiment it was investigated the possibility of using intravaginal devices for P4 supplementation. There was no difference in the levels of P4 in females from groups 1g and 1,9g of P4, however, both groups showed lower levels in relation to group 3,8g P4. It is concluded that the management and the hormone injections of the AIL protocol does not promote significant stress and inflammatory reaction, being the long period of estrus manifestation the main inconvenience. The levels of progesterone observed suggest the possibility of using intravaginal devices to replace daily progesterone injections. The information obtained in this study will support the improvement of protocols for lactation induction.